Men’s views on factors contributing to their poor health-seeking behaviour in Limpopo Province, South Africa - Lazarros Chavalala; Tsakani Rachel Lebese; Lufuno Makhado (BMC Public Health)
Abstract Background The reasons for men not to seek healthcare seem similar across the world. They avoid going for regular medical check-ups, and preventive care and often disregard symptoms or delay seeking medical attention when sick, in pain, or even when their lives are in danger. Methods This study sought to explore the views of men on factors contributing to poor health-seeking behavior among men in Mopani, Vhembe, and Capricorn district municipalities in Limpopo Province. A qualitative descriptive design was used and individual semi-structured interviews were used to collect data in May and June 2024 from 21 men who were purposively selected. Collected data were audio recorded and transcribed verbatim for analysis. Tech’s eight steps were used to analyse data and guide the development of emerged main themes and sub-themes. Trustworthiness was ensured through credibility, confirmability, dependability, and transferability. Ethical approval was obtained from the University of Venda research ethics committee with Ethics Approval Number: FHS/21/PH/26/1215. Results Self-medication, fear of knowing own health status, peer and community elders’ influence, stigma, and masculinity beliefs were among the reasons participants avoided utilizing health services. Educational and health promotional campaigns, challenging societal norms, and employing more nurses were suggested as strategies to improve men’s health-seeking behaviour. Conclusions It is evident from the findings that several factors contribute to men’s poor health-seeking behaviour including visiting health facilities to seek needed healthcare services. Self-treating of disease at hand, fear of knowing own health status, use of traditional healers, and sticking to cultural values are among the factors that contribute to men’s poor health-seeking behaviour. There is a need to challenge societal norms and how men are raised as factors that contribute to poor health-seeking behaviour among men.